Does the Dispersion of Unit Labor Cost Dynamics in the EMU Imply Long-run Divergence? Results from a Comparison with the United States of America and Germany - Sebastian Dullien; Ulrich Fritsche (Hamburg University, Department Economics and Politics, 2007)
Using unit labor cost (ULC) data from Euro area countries as well as US States and German Laender we investigate inflation convergence using different approaches, namely panel unit root tests, cointegration tests and error-correction models. All in all we cannot reject convergence of ULC growth in EMU, however, country-specific deviations from the rest of the currency union are more pronounced in Europe and more persistent. This holds before and after the introduction of the common currency.
Keywords: E31; O47; C32; 330; Unit labor costs; inflation; EMU; convergence; panel unit root tests; convergence clubs